(untitled) (Revista Contexto & Saúde, 2025)
This cross-sectional study determines the prevalence of addictive eating behavior among university students in the southern region of Brazil amid social distancing by the COVID-19 pandemic. Data were collected sociodemographic characteristics, anthropometric parameters, previous eating frequency and eating during social distancing, and duration of social distancing using an online self-report questionnaire. The modified Yale Food Addiction Scale 2.0 was also used. A total of 1525 students aged between 18 and 60 participated in the study, who were majority female, white, single, and from the state of Rio Grande do Sul. The prevalence of addictive eating behavior was 18%. Addictive eating behavior was found to be associated with being a female (PR=1.80; 95% CI 1.32–2.47), being between the ages of 18 and 33 (PR=5.12; 95% CI 1.44–18.3), being divorced (PR=2.46; 95% CI 1.41–4.27), an increased BMI 12 months after social distancing (PR=2.31; 95% CI 1.40–3.82); and decreased (PR=1.63; 95% CI 1.18–2.27) and increased (PR=2.18; 95% CI 1.31–2.79) number of meals per day. This study assessed the prevalence of addictive eating behaviors among university students in the southern region of Brazil during the COVID-19 pandemic, indicating that the COVID-19 pandemic negatively impacted Brazilian academics.